A CMOS line driver for ADSL central office applications. - Bicakci, A.
An ADSL central office (CO) line driver utilizing a single 6-V supply is described. The line driver output produces a 20-Vppd signal to deliver a 40-Vppd swing to a 100-Ω line. The adoption of an active termination, a dynamic supply control circuit technique, and deep n-well devices at the output stage of the line driver is key in achieving such a large voltage swing in a 0.25-μm CMOS process. In order to ensure reliability of the output devices, the dynamic supply control algorithm is designed to activate only one lift amplifier at each signal path of the differential line driver at any given time. A transformer turns ratio of 1:2.4 ensures both reliability and optimal power dissipation in the presence of system losses. The total power dissipation of the line driver is 700 mW when discrete multitone signals with a crest factor of 15 dB were used to deliver 20.4 dBm to a 100-Ω line.
Keywords: 15 dB; 1:2.4 transformation; 6 V; 700 mW; ADSL CO line driver; ADSL central office applications; CMOS analog integrated circuits; CMOS line driver; Active termination; Crest factor; Deep n-well devices; Differential line driver; Discrete multitone signals; Driver circuits; Dynamic supply control algorithm; Dynamic supply control circuit technique; High-voltage techniques; Line driver output; Offset calibration; One lift amplifier; Optimal power dissipation; Output device reliability; Power amplifiers; Signal path; Transformer turns; Voltage swing; Wire communication; 0.25-μm CMOS process; 100-Ω line; 20-Vppd signal; 40-Vppd swing